Compilation of 29 years of postmortem examinations identifies major shifts in equine parasite prevalence from 2000 onwards. Issue 2 (February 2020) - Sallé, G.; Guillot, J.; Tapprest, J.; Foucher, N.; Sevin, C.; Laugier, C.
Graphical abstract: ANSES, Laboratoire de pathologie équine: Highlights: Parasite loads of 1, 673 young horses examined at necropsy over 29 years were analysed. Parasite burden varied across season and was reduced in race horses. Fatal Parascaris spp. and cyathostomin infections have been on the rise since 2000. Available deworming history data was compatible with lower drug efficacy after 2000. Abstract: Horses are infected by a wide range of parasite species that form complex communities. Parasite control imposes significant constraints on parasite communities whose monitoring remains, however, difficult to track through time. Postmortem examination is a reliable method to quantify parasite communities. Here, we compiled 1, 673 necropsy reports accumulated over 29 years, in the reference necropsy centre from Normandy (France). The burden of non-strongylid species was quantified and the presence of strongylid species was noted. Details of horse deworming history and the cause of death were registered. Building on these data, we investigated the temporal trend in non-strongylid epidemiology and we determined the contribution of parasites to the deaths of horses throughout the study period. Data analyses revealed the seasonal variations of non-strongylid parasite abundance and reduced worm burden in race horses. Beyond these observations, we found a shift in the species responsible for fatal parasitic infection from the year 2000 onward, whereby fatal cyathostominosis and Parascaris spp. infection have replaced cases of death caused by Strongylus vulgaris and tapeworms. A concomitant break in the temporal trend of parasite species prevalence was also found within a 10 year window (1998–2007) that has seen the rise of Parascaris spp . and the decline of both Gasterophilus spp. and tapeworms. A few cases of parasite persistence following deworming were identified, which all occurred after 2000. Altogether, these findings provide insights into major shifts in non-strongylid parasite prevalence and abundance over the last 29 years. They also underscore the critical importance of Parascaris spp . in young equids.